Analisis Hubungan Struktur Kepemilikan Manajerial, Nilai Perusahaan dan Investasi Dengan Model Persamaan Linear Simultan - Eddy Suranta; Pratana Puspa Midiastuty (The Indonesian Journal of Accounting Research, 2013)
The research is purported to observe the influence of managerial ownership and board size toward firm value and investment. The empirical examination is carried out in two regression model namely the ordinary least square which purpose to observe a non-monotonic relationship between the managerial ownership toward firm value and investment. The second regression model used a simultaneous equation system of the two-stage least square (2SLS) to observe if firm value and investment influenced by managerial ownership and board size.The results of empirical examination using OLS indicate that managerial ownership relationship and firm value are linear and negative and using 2SLS indicate a similar result with result of OLS regression. This result indicated that the managerial ownership constitute exogenous variable toward firm value. The next examination results in using OLS indicate managerial ownership cannot be predicting influence and using 2SLS the result is different by paramater estimation. The whole results gives evidence that managerial ownership constitute exogenous variable. The final examination result indicates that shareownership by board of director and a commissioner as exogenous variables toward firm value and investment.